contestada

Sasha is solving a multi-step equation. Her first step is shown below.
Equation: 3x - 8 - 10x = 3(2x + 3)
Step 1: 3x - 10x - 8 = 6x + 9
Which properties did Sasha use to get to Step 1? Select all that apply.
A. addition property of equality
B. associative property of addition
C. commutative property of addition
D. multiplication property of addition
E. distributive property of multiplication over addition.

Respuesta :

Answer:

E. distributive property of multiplication over addition.

Step-by-step explanation:

Expand the following:

(-7 x - 8 = 3 (2 x + 3), Sort[True], -7 x - 8 = 6 x + 9)

Hint: | Distribute 3 over 2 x + 3.

3 (2 x + 3) = 3 (2 x) + 3 3:

(-7 x - 8 = 3 2 x + 3 3, Sort[True], -7 x - 8 = 6 x + 9)

Hint: | Multiply 3 and 3 together.

3×3 = 9:

(-7 x - 8 = 3 2 x + 9, Sort[True], -7 x - 8 = 6 x + 9)

Hint: | Multiply 3 and 2 together.

3×2 = 6:

(-7 x - 8 = 6 x + 9, Sort[True], -7 x - 8 = 6 x + 9)

Hint: | Move terms with x to the left hand side.

Subtract 6 x from both sides:

((-7 x - 6 x) - 8 = (6 x - 6 x) + 9, Sort[True], -7 x - 8 = 6 x + 9)

Hint: | Combine like terms in -7 x - 6 x.

-7 x - 6 x = -13 x:

(-13 x - 8 = (6 x - 6 x) + 9, Sort[True], -7 x - 8 = 6 x + 9)

Hint: | Look for the difference of two identical terms.

6 x - 6 x = 0:

(-13 x - 8 = 9, Sort[True], -7 x - 8 = 6 x + 9)

Hint: | Isolate terms with x to the left hand side.

Add 8 to both sides:

((8 - 8) - 13 x = 8 + 9, Sort[True], -7 x - 8 = 6 x + 9)

Hint: | Look for the difference of two identical terms.

8 - 8 = 0:

(-13 x = 9 + 8, Sort[True], -7 x - 8 = 6 x + 9)

Hint: | Evaluate 9 + 8.

9 + 8 = 17:

(-13 x = 17, Sort[True], -7 x - 8 = 6 x + 9)

Hint: | Divide both sides by a constant to simplify the equation.

Divide both sides of -13 x = 17 by -13:

((-13 x)/(-13) = 17/(-13), Sort[True], -7 x - 8 = 6 x + 9)

Hint: | Any nonzero number divided by itself is one.

(-13)/(-13) = 1:

(x = 17/(-13), Sort[True], -7 x - 8 = 6 x + 9)

Hint: | Simplify the sign of 17/(-13).

Multiply numerator and denominator of 17/(-13) by -1:

(x = (-17)/13, Sort[True], -7 x - 8 = 6 x + 9)

Hint: | Move terms with x to the left hand side.

Subtract 6 x from both sides:

(x = -17/13, Sort[True], (-7 x - 6 x) - 8 = (6 x - 6 x) + 9)

Hint: | Combine like terms in -7 x - 6 x.

-7 x - 6 x = -13 x:

(x = -17/13, Sort[True], -13 x - 8 = (6 x - 6 x) + 9)

Hint: | Look for the difference of two identical terms.

6 x - 6 x = 0:

(x = -17/13, Sort[True], -13 x - 8 = 9)

Hint: | Isolate terms with x to the left hand side.

Add 8 to both sides:

(x = -17/13, Sort[True], (8 - 8) - 13 x = 8 + 9)

Hint: | Look for the difference of two identical terms.

8 - 8 = 0:

(x = -17/13, Sort[True], -13 x = 9 + 8)

Hint: | Evaluate 9 + 8.

9 + 8 = 17:

(x = -17/13, Sort[True], -13 x = 17)

Hint: | Divide both sides by a constant to simplify the equation.

Divide both sides of -13 x = 17 by -13:

(x = -17/13, Sort[True], (-13 x)/(-13) = 17/(-13))

Hint: | Any nonzero number divided by itself is one.

(-13)/(-13) = 1:

(x = -17/13, Sort[True], x = 17/(-13))

Hint: | Simplify the sign of 17/(-13).

Multiply numerator and denominator of 17/(-13) by -1:

Answer: (x = -17/13, Sort[True], x = (-17)/13)